Religiosity and Literacy of Islamic Banks: Analysis Islamic Banks Customers in Jakarta - Zulfison Zulfison (Indonesia Banking School, 2019)
The Islamic banking industry began in 1992 since then, the industry has continued to grow and develop. Despite the potential value of Islamic banks, research has yet to identify the decision factors of the custom-ers to choose them. Some of the factors have been investigated includes social factors as one of the varia-bles sought to influence the decision using Islamic banks, and the past study revealed that factor social has an influence on customers' decisions to use Islamic banks. Nevertheless, the social factors are still very broad and based on the data and previous research, there are conflicting results and differences in the re-sults of each previous study that the author has reviewed. Thus, the current study is interested in research-ing whether factors such as religiosity, reference groups and knowledge about Islamic banks have influ-ence to the customer's decision to use Islamic banking.